Safety and nonclinical and clinical pharmacokinetics of PC945, a novel inhaled triazole antifungal agent. Issue 1 (19th December 2020) - Cass, Lindsey; Murray, Alison; Davis, Amanda; Woodward, Kathy; Albayaty, Muna; Ito, Kazuhiro; Strong, Pete; Ayrton, John; Brindley, Charlie; Prosser, Jayne; Murray, John; French, Eddie; et al.
Abstract: PC945 is a novel antifungal triazole formulated for nebulized delivery to treat lung Aspergillus infections. Pharmacokinetic and safety profiles from nonclinical studies and clinical trials in healthy subjects, and subjects with mild asthma were characterized. Toxicokinetics were assessed following daily 2‐hour inhalation for 14 days. Potential for drug‐drug interactions was evaluated using pooled human liver microsomes. Clinical safety and pharmacokinetics were assessed following (a) single inhaled doses (0.5‐10 mg), (b) 7‐day repeat doses (5 mg daily) in healthy subjects; (c) a single dose (5 mg) in subjects with mild asthma. C max occurred 4 hours (rats) or immediately (dogs) after a single dose. PC945 lung concentrations were substantially higher (>2000‐fold) than those in plasma. PC945 only inhibited CYP3A4/5 substrate metabolism (IC50 : 1.33 µM [testosterone] and 0.085 µM [midazolam]). Geometric mean C max was 322 pg/mL (healthy subjects) and 335 pg/mL (subjects with mild asthma) 4‐5 hours (median tmax ) after a single inhalation (5 mg). Following repeat, once daily inhalation (5 mg), Day 7 C max was 951 pg/mL (0.0016 µM) 45 minutes after dosing. Increases in C max and AUC0–24h were approximately dose‐proportional (0.5‐10 mg). PC945 administration was well tolerated in both healthy subjects and subjects with mild asthma. Treatment‐emergent adverse events were mild/moderate and resolved before the study ended. No clinically significant lung function changes were observed. PC945 pharmacokinetics translated from nonclinical species to humans showed slow absorption from lungs and low systemic exposure, thereby limiting the potential for adverse side effects and drug interactions commonly seen with systemically delivered azoles. Abstract : PC945 pharmacokinetics translated from nonclinical species to humans showed slow absorption from lungs and low systemic exposure, thereby limiting the potential for adverse side effects and drug‐drug interactions commonly seen with systemically delivered azole antifungals.